Pharmacological prevention of post‐operative pancreatitis: systematic review and meta‐analysis of randomized controlled trials on animal studies. Issue 6 (22nd December 2021) - Cecire, Jack; Adams, Kristian; Pham, Helen; Pang, Tony; Burnett, David
Abstract: Background: Postoperative pancreatic fistula (POPF) remains a significant complication of pancreatic resection with recent evidence showing a strong association between post‐operative pancreatitis and subsequent development of POPF. Incidence and severity of pancreatitis following endoscopic therapy has been effectively reduced with indomethacin prophylaxis, however further agents require evaluation. We present a systematic literature review and meta‐analysis of the prophylactic treatment with corticosteroids or n‐acetyl cysteine (NAC) of induced pancreatitis in rodent models. Methods: A systematic literature search was conducted using Pubmed, Medline, Embase and Cochrane library to identify eligible randomized control trials (RCT) involving animal models that examined NAC or corticosteroids. The primary outcome was the subsequent effect on serum amylase and IL‐6 and the histopathological markers of severity such as pancreatic oedema and necrosis. Results: Four RCTs ( n = 178) met inclusion criteria examining NAC and eight RCTs ( n = 546) examining corticosteroid agents (dexamethasone, hydrocortisone, methylprednisolone). Prophylactic administration of all corticosteroid agents showed a net effect in favour of reducing markers of severity of pancreatitis. NAC showed a significant reduction in severity of amylase and necrosis. Conclusion: The RCTs examined suggest that prophylactic administration of corticosteroid agents and NAC can reduce the severity of pancreatitis as indicated by histopathologic markers, serum amylase and IL‐6 levels. Abstract : Postoperative pancreatic fistula (POPF) remains a significant complication of pancreatic resection with recent evidence showing a strong association between perioperative pancreatitis and the subsequent development of POPF. We present a systematic literature review and meta‐analysis of the prophylactic treatment with corticosteroids or n‐acetyl cysteine (NAC) of induced pancreatitis in animal models.